Ban on Mobile Phone Usage Among Secondary School Students: Catalyst for Academic Succes - Ruth Asemota; Edinoh Kingsley; Oladejo Bolaji (International Journal on Integrated Education, 2026)
The rapid integration of mobile technology into educational settings has intensified debate over its influence on students’ academic performance. This study examines whether banning mobile phone use in secondary schools contributes to improved academic outcomes. A mixed-method design was employed, involving 240 secondary school students and 40 teachers across six schools in North Central Nigeria. Data were collected through structured questionnaires and students’ academic records. Quantitative data were analysed using descriptive statistics, Pearson correlation, and regression analysis, while qualitative data were thematically analysed. Findings indicate a significant negative relationship between excessive mobile phone use and academic performance (r = -0.62, p <0.05). Conversely, regulated or restricted use was associated with improved concentration, increased classroom engagement, and better learning outcomes. Schools implementing mobile phone bans recorded significantly higher mean academic scores than those without such policies. The study concludes that while unrestricted mobile phone use can hinder academic success, structured regulation enhances student performance. However, outright bans should be complemented by digital literacy initiatives that promote responsible and educational use of technology. The study recommends the adoption of balanced school policies that integrate restriction, monitoring, and purposeful technological engagement to optimise learning outcomes.